PERPUSTAKAAN DIGITAL PADA PERGURUAN TINGGI DENGAN KONSEP KNOWLEDGE MANAGEMENT - Endang Retnoningsih (LPPM Universitas Bina Sarana Informatika, 2013)
The need for information in the higher age of globalization, we need a breakthrough that canfacilitate the acquisition of information. Along with this, various methods undertaken to developthe knowledge and information for the community, one with Knowledge management models,which include information technology in knowledge processing. In the world of education, thelibrary is the source of all mine of information, to the library in the need for an information systemthat makes it easy for users (especially students and lecturers) to obtain reference knowledge aspossible, accurate, and fast. Knowledge management takes its role in the development of digitallibrary information system to create, capture, and reuse knowledge to achieve the goal. In thiscase the university can develop a digital library system based Knowledge management in order tosupport the development activities for the academic community to the world-class universities onresearch oriented.Keyword : Library Information Systems, Digital Libraries, Knowledge Management